Mathematical Modeling and Numerical Analysis of SPIM Drive Using Modified SVPWM Technique - Rathore, Vishal; Yadav, Krishna Bihari (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2022)
This paper presents a modified space-vector pulse width modulation (SVPWM) technique for a five-level inverter that provides complete control over the multiple space-vector voltages of a six-phase inverter. This technique involves splitting six phases into two three-phase five-level inverters connected in parallel. A six-phase induction motor (SPIM) drive with a distributed neutral is considered as the load. This paper also presents a comparative analysis between the proposed and conventional SVPWM inverter-fed SPIM drives. To investigate the analytical developments and voltage limits, MATLAB/Simulink environment was used in this study. A prototype was developed in the laboratory for analyzing the harmonic components of the phase voltages and currents. The efficacy of the proposed technique was validated by means of comprehensive experiments, and the results discussed herein.